Racial and Economic Diversity in U.S. Public Montessori Schools - Debs, Mira Catherine (Journal of Montessori Research, 2016)
As public Montessori schools rapidly expand through the United States, the question then arises: What population of students do the schools serve? This study presents a new empirical data set examining the racial and economic diversity of 300 whole-school, public Montessori programs open in 2012–2013, where the entire school uses the Montessori Method. While school-choice scholars are concerned that choice programs like Montessori lead to greater student segregation by race and social class, this study finds a variety of outcomes for public Montessori. Public Montessori as a sector has strengths in student racial and socioeconomic diversity, but it also has diversity challenges, particularly among Montessori charters. The study concludes with recommended strategies for public Montessori schools to enroll a racially and economically diverse student body.